The Integrated Impact of Metabolic, Dietary, Environmental, and Psychological Factors on Psoriasis – An Interdisciplinary Perspective on an Inflammatory Skin Disease - Witkowska, Edyta; Ciechański, Marcin; Wilk, Klaudia; Cholewiński, Szymon; Wilk, Bernadetta; Stachura, Piotr; Rejman, Piotr; Pszczoła, Katarzyna; Jurkiewicz, Katarzyna; Kasprzyk, Aleksandra (Quality in Sport, 2025)
Introduction, purpose: Psoriasis is a chronic, non-infectious skin disease. It is estimated that approximately 2–3% of the global population is affected by this condition. Its prevalence varies geographically — higher rates are observed in Europe and North America, while lower rates are noted in Asia and Africa. The development of psoriasis is influenced by genetic predisposition, immune system dysfunction, as well as environmental factors. Psoriasis is not only a dermatological issue characterized by excessive keratinocyte proliferation, but also a systemic inflammatory disease that impacts the patient’s psycho-emotional well-being and carries an increased risk of numerous complications. Materials and methods: A literature review was conducted using the PubMed database to analyze the impact of patients' lifestyle on the course of psoriasis and the development of complications associated with this condition. Basic results: A holistic approach to patient care, which takes into account the various factors influencing the course of the disease and identifies areas of life that can be modified to enhance the overall health of the patient, is of significant importance in the pathogenesis of psoriasis. Conclusions: Although topical and systemic medications remain the cornerstone of psoriasis treatment, lifestyle modifications and health-promoting behaviors can contribute to a milder disease course, reduce the frequency of relapses, and lower the risk of comorbidities.